Enhanced photoelectrochemical water splitting performance using morphology-controlled BiVO4 with W doping - Zhao, Xin; Chen, Zhong (Beilstein Journal of Nanotechnology, 2017)
Nanostructures exhibit numerous merits to improve the efficiency in solar-to-energy conversion. These include shortened carrier collection pathways, an increased volume ratio between depletion layer and bulk, enhanced light capture due to multiple light scattering in nanostructures, and a high surface area for photochemical conversion reactions. In this study, we describe the synthesis of morphology-controlled W-doped BiVO4 by simply tuning the solvent ratio in precursor solutions. Planar and porous W-doped BiVO4 thin films were prepared and compared. The porous film, which exhibits increased surface area and enhanced light absorption, has displayed enhanced charge separation and interfacial charge injection. Our quantitative analysis showed an enhancement of about 50% of the photoelectrochemical performance for the porous structure compared to the planar structure. This enhancement is attributed to improved light absorption (13% increase), charge separation (14% increase), and interfacial charge injection (20% increase).
Keywords: bismuth vanadate; charge separation; nanostructure; photoelectrochemical water splitting